Influence of SARS-CoV-2 infection before and during organogenesis on embryo implantation and development outcomes: A prospective cohort observational study - Yanping Li; Xuan Lu; Jing Fu; Fan Yang; Zenghui Mao; Hongqing Liao; Juan Zhang; Xianghong Huang; Qiong Zhang (PLoS ONE, 2025)
Background Extensive research has demonstrated the detrimental effects of COVID-19 on maternal-fetal outcomes. However, few studies have examined the impact of SARS-CoV-2 infection before and during organogenesis on human embryo implantation and subsequent development. Additionally, the influence of SARS-CoV-2 on the endometrial microenvironment, which is critical for embryo implantation, remains poorly understood. This study seeks to address these gaps in knowledge. Methods and findings We prospectively enrolled 971 participants undergoing frozen-thawed embryo transfer (FET) during the final two months of 2022, coinciding with the nationwide COVID19 outbreak following the end of China’s Zero-Covid policy. Patients undergoing FET during this period were at high risk of SARS-CoV-2 infection before and during organogenesis. Based on self-reported symptoms and nucleic acid testing, 520 individuals were confirmed to have SARS-CoV-2 infection, while 451 were uninfected. Consistent with existing literature, our study reinforced that SARS-CoV-2 infection negatively impacted pregnancy outcomes, as evidenced by reduced clinical pregnancy (52.69% vs. 76.50%, RR = 60.506, [95%CI, 0.259 ~ 0.452]) and live birth rates (46.54% vs. 60.09%, RR = 17.865, [95%CI, 0.448 ~ 0.746]), alongside an increase in obstetric complications (35.89% vs. 27.37%, RR = 4.380, [95%CI, 1.055 ~ 2.223]). Seven fetal congenital heart defects (CHDs) were observed in the infected group versus one in uninfected population. Bioinformatic analysis of endometrial mRNA profiles showed SARS-CoV-2 infection significantly downregulated key endometrial receptivity molecules, increased natural killer cell and mast cell infiltration, and disrupted the balance of cytokine and chemokine. Moreover, our findings demonstrated that SARS-CoV-2 infection downregulated the transcriptional activity of endometrial SLC6A, a serotonin transporter, and ErbB-2, a mediator of serotonin-regulated differentiation in cardiac development. This disruption in serotonin signaling may underlie the pathogenesis of congenital heart disease. Conclusions SARS-CoV-2 infection before and during organogenesis negatively impacts embryo implantation and development, primarily through mechanisms involving compromised endometrial receptivity and disruption of the local immune microenvironment.